2019
DOI: 10.1007/s40271-019-00374-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Infusion Frequency in Hemophilia A: Exit Interviews with Patients Participating in BAY 94-9027 Extension Studies (PROTECT VIII)

Abstract: IntroductionProphylactic treatment of severe hemophilia A is burdensome, requiring frequent intravenous injections. Extended half-life (EHL) factor VIII replacement therapies offer longer intervals between infusions while still meeting efficacy and safety outcomes; however, patient perspectives following long-term use of such products in the real-world remain unknown.ObjectiveWe aimed to explore the importance of infusion frequency and the potential benefits of reduced infusion frequency among patients receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…3 Reducing the frequency of injections and extending the protection afforded by each injection will improve patients' quality of life, including improved ability to participate in physical activity and less time needed to administer treatment. 8 Furthermore, the need for fewer injections may improve patient adherence to treatment. 9 This study has both strengths and limitations.…”
Section: Characteristicsmentioning
confidence: 99%
“…3 Reducing the frequency of injections and extending the protection afforded by each injection will improve patients' quality of life, including improved ability to participate in physical activity and less time needed to administer treatment. 8 Furthermore, the need for fewer injections may improve patient adherence to treatment. 9 This study has both strengths and limitations.…”
Section: Characteristicsmentioning
confidence: 99%
“…EHL rFVIII products such as Jivi ® offer the potential for increased protection against bleeds while requiring less frequent infusions and IU consumption. A recent analysis aimed to evaluate patients reported outcomes regarding the benefit of the treatment with an EHL rFVIII therapy with Jivi ® [24,25].…”
Section: Jivi ®mentioning
confidence: 99%
“…More details around the recruitment method and the conduct of the interviews with the patients has been published elsewhere [13].…”
Section: Physician and Patient Interviewsmentioning
confidence: 99%
“…In addition, physicians and study participants from the investigator sites in Israel, the Netherlands and the USA were invited to participate in qualitative exploratory interviews when exiting the extension part of the study. The findings from the patient interviews were recently published and showed that participants reported that BAY 94-9027 received during the PROTECT VIII study resulted in their increased ability to participate in physical activities, better 'vein health', less time needed to schedule and administer factor VIII, reduced impact on work and improved emotional well-being [13].…”
Section: Introductionmentioning
confidence: 99%